Ray - Baldwin, Howard; Hackford, Taylor; Foxx, Jamie; Universal Pictures; Bristol Bay Productions (Universal City, CA : Universal, 2005)
Ray Charles went blind at the age of seven. Inspired by his mother who insisted he make his own way, he found his calling at the keyboard.'Ray' follows as he overcomes drug addiction while becoming one of the country's most beloved performers
title from title screen
Subtitles in English, Thai, Indonesian, Cantonese, Mandarin Tradisional
Screenplay by James L. White ; story, Taylor Hackford and James L. White ; Director of photography, Pawel Edelman ; art director, Scott Plauche ; editor, Paul Hirsch ; music, Craig Armstrong, Ray Charles ; costume designer, Sharen Davis ; production designer, Stephen Altman ; visual effects, Chad Dombrova
Casts: Jamie Foxx, Kerry Washington, Regina King, Clifton Powell, Harry Lennix, Bokeem Woodbine, Aunjanue Ellis, Sharon Warren, C.J. Sanders
Keywords: Charles, Ray, -- 1930-2004 -- Drama; Blind entertainers -- Drama